1902 La. Acts 150, in 2 Solomon Wolff, Constitution and Revised Laws of Louisiana 1718 (1904) - (:unkn) unknown (My University, 1903)
Imposed a license tax of ten dollars on all wholesale dealers of pistols and rifles, and a five dollar license tax on wholesale dealers of pistol and rifle cartridges. Imposed a one hundred dollar license tax on retail dealers of pistols and rifles and a fifty dollar tax on retail dealers of pistol and rifle cartridges. Also provided that any person who shall sell pistols, rifles, pistol cartridges, or rifle cartridges without paying the license tax is guilty of a misdemeanor
Keywords: LICENSE - DEALERS